Effect of astrocyte GPER on the optic nerve inflammatory response following optic nerve injury in mice - Xuan Wang; Jiaxing Zhou; Yuwen Wang; Xue Li; Qiumei Hu; Linlin Luo; Xuemei Liu; Wei Liu; Jian Ye (Heliyon, 2024)
Activated astrocytes are a primary source of inflammatory factors following traumatic optic neuropathy (TON). Accumulation of inflammatory factors in this context leads to increased axonal damage and loss of retinal ganglion cells (RGCs). Therefore, in the present study, we explored the role of the astrocyte G protein-coupled estrogen receptor (GPER) in regulating inflammatory factors following optic nerve crush (ONC), and analyzed its potential regulatory mechanisms. Overall, our results showed that GPER was abundantly expressed in the optic nerve, and co-localized with glial fibrillary acidic proteins (GFAP). Exogenous administration of G-1 led to a significant reduction in astrocyte activation and expression of inflammation-related factors (including IL-1β, TNF-α, NFκB, and p-NFκB). Additionally, it dramatically increased the survival of RGCs. In contrast, astrocytes were activated to a greater extent by exogenous G15 administration; however, RGCs survival was significantly reduced. In vitro, GPER activation significantly reduced astrocyte activation and the release of inflammation-related factors. In conclusion, activation of astrocyte GPER significantly reduced ONC inflammation levels, and should be explored as a potential target pathway for protecting the optic nerve and RGCs after TON.